A 2-D distributed power combining by metamaterial-based zero phase shifter for 60-GHz power amplifier in 65-nm CMOS - Fei, Wei (2013)
Based on a newly introduced zero-phase-shifter (ZPS), a 2D distributed power combining network is developed in this paper to provide simultaneous distributed amplification and power combining. One type of metamaterial called composite right/left handed transmission line (CRLH T-line) is deployed to design ZPS with detailed considerations to achieve low loss and wideband performance. The proposed 2D distributed power combining is implemented for one 60GHz PA design by UMC standard 65nm CMOS process. Measured results show that the fabricated PA has 0.39mm2 area, 8.3dB gain, 7.1% PAE, and 9.7dBm P1dB with 16GHz bandwidth (44 to 60GHz).